Can the Leadership Sense of Duty of Gen Z Be Bought? Evidence from Malaysian Gen Z Students - Toh, Seong-Yuen *; Lim, Shue-Li*; Kaur, Ranita*; Too, Choon-Teng* (Sage, 2022)
Gen Z constitutes 29% of Malaysia’s population and a growing proportion of the workforce in the near future. Very little is known about their leadership potential. This study investigates whether Gen Z’s sense of duty to lead can be influenced by rewards. Extant literature characterizes Gen Z as convenience-oriented, reward-seeking, calculative, independent, idealistic, and optimistic. An anonymous online questionnaire was used to survey students in schools and universities in Malaysia, targeting respondents 25 years old and below to represent the Gen Z cohort. A total of 153 valid cases were used for statistical analysis. Contrary to their purported self-serving and entitled sentiments, the evidence in this study suggests that Malaysian Gen Z’s sense of duty to lead cannot be easily swayed by rewards. We further found that they do not necessarily dislike working in groups as claimed by past studies; instead, they avoid conflict and discord in teamwork if possible and therefore prefer to work independently if team disharmony is inevitable. While the literature on Gen Z indicates that they prefer convenience, comfort, and are self-interested, this study suggests that their sense of duty to lead can be sacrificial and selfless.